Essays in Zen Buddhism, first series - Suzuki, Daisetz Teitaro (Rider, 1970)
This book is collection of the essays orignally published in the Eastern Buddhist, except one on the History of Zen Buddhism which was written specially for this volume; but all of them have been thoroughly revised and in some parts entirely rewritten and new chapters added,...